COMPREHENSIVE THERAPY FOR POLYCYSTIC OVARY SYNDROME: KEY POINTS TO IMPROVE QUALITY OF LIFE - Putri, Noviyati Rahardjo; Widyawati, Melyana Nurul (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder that affects the hypothalamus, pituitary, and ovary. PCOS prevalence has increased from 4 ?6% to 8 ?10%. This syndrome results in both physical illnesses and psychological disorders. Women with PCOS tend to be more prone to psychological disorders compared to healthy women. PCOS increases the risk of anxiety by 7 folds. This study aims to analyze measures to reduce psychological disorders caused by PCOS based on numerous psychological disorder parameters and hormonal biomarkers with psychological therapies.Methodology: This study is based on the PRISMA protocol guidelines. The literature review was performed by accessing ScienceDirect, PubMed, Sage Publications and Google Scholar. The inclusion criteria for the articles are full-text papers written by English from 2009 to 2018. The keywords used to find suitable articles are ?anxiety, stress, distress, depression, and quality of life management in polycystic ovary syndrome?. Nine articles were subsequently reviewed.Results: Psychological therapies that can be applied for PCOS include holistic yoga, acupuncture, spiritual guidance, mindfulness stress management, relaxation, and guided imagery, progressive muscle relaxation and administration of herbal, probiotic and selenium medication. Those therapies have proven to lower anxiety, stress, depression, and psychological fatigue as they were measured using instruments of Montgomery A?sberg Depression Rating Scale (MADRS-S), Brief Scale for Anxiety (BSA- S), Swedish Short-Form36 (SF-36), PCOS Questionnaire (PCOSQ), Beck Depression Inventory, DASS 21 and STAI. Meanwhile, observed biomarker responses include lower levels of cortisol, adrenalin, testosterone, and malondialdehyde (MDA) and a higher level of endorphin. Conclusion: Psychological therapies for PCOS have proven to lower psychological disorders as measured by numerous parameters and biomarkers. Therefore, psychological therapies have to be further developed to decrease psychological disorders because of Polycystic Ovary Syndrome. Such as symptoms of anxiety and prevent deterioration of social mental health.